ECOCRITICAL REPRESENTATIONS OF DISASTER IN DENNY JA’S ESSAY POEM, THE NAME OF DISASTER - Kartika Kartika; Hidayatun Nur (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates the representation of the human–nature relationship in the essay poems of Atas Nama Bencana by Denny JA through the lens of Lawrence Buell’s ecocritical theory. While previous studies on Denny JA’s essay poetry have predominantly examined social, political, and humanitarian concerns, ecological dimensions and environmental representations remain insufficiently explored. Moreover, the application of Buell’s ecocritical framework to contemporary Indonesian essay poetry has received limited scholarly attention. Addressing this gap, the study explores how ecological values and environmental criticism are articulated within the poems. Employing a descriptive qualitative design with a content analysis approach, the research examines words, phrases, lines, and stanzas related to ecological issues across ten essay poems in the collection. Data were gathered through close reading, note-taking, and classification techniques and analyzed using Buell’s four ecocritical principles. The findings reveal that ecological disasters are portrayed not merely as natural occurrences but as consequences of anthropocentric exploitation and environmental negligence. Two dominant patterns emerge: nature is represented as an active agent capable of responding to human actions, and environmental degradation is depicted as both a moral and social crisis. Through the interconnected imagery of forests, rivers, rain, floods, and landslides, the poems challenge anthropocentric perspectives and promote ecological awareness. The study demonstrates the relevance of Buell’s ecocritical framework in uncovering environmental ethics embedded in contemporary Indonesian literature, positioning Atas Nama Bencana as both an aesthetic work and a vehicle for ecological critique.